The Biological and Pharmacological Potentials of Indole-based Heterocycles - Sharma, Shivangi; Singh, Shivendra (Letters in Organic Chemistry, 2023)
An important bioactive heterocycle having several uses in medicinal chemistry, synthetic organic chemistry, material chemistry, and natural product is indole along with its analogues. Many bioactive indole-based heterocycles have important antibacterial, anti-inflammatory, analgesic, antiviral, antimalarial, chemotherapeutic, antifungal, and anti-TB effects, as well as antioxidant capabilities. Several well-known medications, including tadalafil, rizatriptan, sumatriptan, and fluvastatin are indole- based potential bioactive compounds. Based on the existing and latest evidence, researchers have focused on developing indole-based compounds with novel biological and pharmacological properties for decades. Owing to useful bioactivities, we have described many bioactive indoles and their synthetic methods in this review article.
Keywords: Indole